2022
DOI: 10.1101/2022.03.16.22272467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective visuoconstructional impairment following mild COVID-19 with inflammatory and neuroimaging correlation findings

Abstract: People recovered from COVID-19 may still present complications including respiratory and neurological sequelae. In other viral infections, cognitive impairment occurs due to brain damage or dysfunction caused by vascular lesions and inflammatory processes. Persistent cognitive impairment compromises daily activities and psychosocial adaptation. Some level of neurological and psychiatric consequences were expected and described in severe cases of COVID-19. However, it is debatable whether neuropsychiatric compl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…Since the onset of the pandemic caused by the SARS-CoV-2 virus, evidence has accumulated that some recovered patients from the acute infection episode exhibit cognitive impairment and brain alterations. [1][2][3] Studies have found that even months after recovery from COVID-19 infection, some individuals continue to experience neurological, psychiatric, and cognitive effects. 4,5 Persistent cognitive symptoms have been linked to brain alterations, including cerebral hypoperfusion 6 and hypometabolism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the onset of the pandemic caused by the SARS-CoV-2 virus, evidence has accumulated that some recovered patients from the acute infection episode exhibit cognitive impairment and brain alterations. [1][2][3] Studies have found that even months after recovery from COVID-19 infection, some individuals continue to experience neurological, psychiatric, and cognitive effects. 4,5 Persistent cognitive symptoms have been linked to brain alterations, including cerebral hypoperfusion 6 and hypometabolism.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, even patients with mild COVID-19 also present subtle brain alterations. [1][2][3] It remains unknown which risk factors or clinical profiles distinguish mild COVID-19 patients who may present this alteration from those who do not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation